Tourist tax as a new tax in the Russian tax system since 2025: results of the experiment and levy prospects - E. L. Gulkova; M. V. Karp; M. V. Tipalina (Вестник университета, 2025)
The work reflects controversial issues concerning introduction of a new tourist tax. The purposes of the study are to overview changes in tax legislation from January 1, 2025 in the field of collecting the tourist tax, features of determining its elements; to identify current problems and find ways to solve them. The authors have analysed the results of the experiment on establishment of a resort fee which ended on December 31, 2024. Data on payment receipts, directions of its use and realised activities in the participating subjects (Altai, Krasnodar, Stavropol regions, St. Petersburg, federal territory “Sirius”) has been analysed. The authors come to the conclusion that, based on the results of the experiment, across the participating regions, resort tax revenues are not significant, problems with assessing possible revenues and efficiency of using the received funds have arisen. In order for the new tax to come into effect on January 1, 2025, representative bodies of municipalities should publish the relevant decisions by December 1, 2024. With the widespread introduction of the tourist tax, there may be a need to strengthen tax control as tourists will look for acceptable vacation options, renting accommodation in the private sector, the objects of which are not be in the registers. Accordingly, the problem of the tax control over tax evasion by individuals – landlords of apartments and residential buildings – will become relevant. The obtained results can be used in developing decisions on the collection of the tourist tax, taxation of personal income, and in developing bills to improve provisions of tax legislation.